Atypical Prosody in Asperger Syndrome: Perceptual and Acoustic Measurements - Filipe, Marisa G. (2016)
It is known that individuals with Asperger syndrome (AS) may show no problems with regard to what is said (e.g., lexical content) but tend to have difficulties in how utterances are produced, i.e., they may show prosodic impairments. In the present study, we focus on the use of prosodic features to express grammatical meaning. Specifically, we explored the sentence type difference between statements and questions that is conveyed by intonation, using perceptual and acoustic measurements. Children aged 8 and 9 years with AS (n = 12) were matched according to age and nonverbal intelligence with typically developing peers (n = 17). Although children with AS could produce categorically accurate prosodic patterns, their prosodic contours were perceived as odd by adult listeners, and acoustic measurements showed alterations in duration and pitch. Additionally, children with AS had greater variability in fundamental frequency contours compared to typically developing peers.